The Levels of Marketing Ethics - Abromaitytė-Sereikienė, Laima (Ekonomika, 2005)
The issue of ethics in marketing continues to be a concern for marketing practitioners and researchers. Every business manager would probably agree that ethical implications are often inherent in marketing decisions. This fact has encouraged to turn to the topic of marketing ethics and to analyze the levels of marketing ethics. As an example of differences in the levels of marketing ethics in different countries, the situation in the old free market and in transition economies is compared. Because the analysis of marketing ethics adoption in the companies of transition economies still requires much research, the purposes of the paper are to present and define the levels on which decisions of marketing ethics are made by comparing the situation in transition and old free market economies, and to fill in the gap in the literature on marketing ethics in Lithuania by defining the main tendencies in the marketing ethics adaptation in this country.To attain the objectives of the paper, it presents the development of the theory of marketing ethics and a theoretical background of the levels of marketing ethics adaptation. The levels of marketing ethics are presented in the context of motivation theories and the corporate social responsibility. The paper will also provide scenarios according to which companies meet or should meet the questions pertaining to marketing ethics in the old market and transition economies.